Assessment of pavement concrete blocks design methods - Bahamondes, Rodrigo; Echaveguren, Tomás; Vargas-Tejeda, Sergio (Revista de la Construcción. Journal of Construction, 2013)
The pavements of concrete pavers (PAH) are used as an alternative to traditional paving of low speed driveways. This paper analyze the PAH design methods proposed in Australia, Japan, United States, United Kingdom and India. A range of CBR subgrade between 4% and 20% and traffic levels between 45,000 and 4,500,000 cumulative equivalent axles were used. The performance parameters for design were the stresses, strains and deflections of the subgrade, which were compared with allowable values. Results showed that for CBR> 10% and low traffic levels, all designs converged to a minimum design and also accomplished with the 3 performance parameters used in this research. It was determined that higher levels of traffic and CBR <10%, the methods of the United Kingdom and Japan provides the best performance.